Perkawinan Wanita Hamil Dengan Yang Bukan Menghamilinya di Desa Uraso Kabupaten Luwu Utara Menurut Imam Malik dan Syafi'i - Aldiansyah; Maloko, M. Thahir; Sanusi, Nur Taufiq (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
The main problem in this research is how the marriage of pregnant women with men who are not pregnant in Uraso Village, Kec. Mapdeceng, Kab. North Luwu According to Imam Malik and Shafi'i. The main problems that will be described from the sub-problems are: 1) What are the views of the people of Uroso Village, Kec. Mapdeceng, Kab. North Luwu regarding the marriage of a pregnant woman with a man who did not impregnate her? 2) What is the opinion of Imam Malik and Syafi'i on the marriage of a pregnant woman with a man who did not impregnate her in Uroso Village, Kec. Mapdeceng, Kab. North Luwu?. The type of research used is qualitative research or field research which describes the phenomena that occur in society and aims to produce descriptive data in the form of data, images and behavior of the people observed using a syar'i normative approach sourced from the arguments of the Qur'an, the hadith of the Prophet as well as the ijtihad of the Ulama and the sociological approach. The data sources in this research are sourced from primary data and secondary data. The results of this study indicate that: 1) Regarding the views from interviews with several community and religious leaders, they have different opinions regarding this phenomenon. 2) The scholars agree on the permissibility of marrying adulterers for those who commit adultery. Thus, the marriage of a pregnant woman with a man who impregnates her or commits adultery is legal and they may have intercourse as husband and wife. Meanwhile, the views of Imam Malik and Shafi'i regarding the marriage of a pregnant woman with a man who did not impregnate her have different opinions. Imam Malik is of the opinion that the marriage is invalid. This is because women who have sexual intercourse with adultery have exactly the same legal status as women who have sexual intercourse with syubhat. The woman must purify herself at the same time as the 'iddah of the woman whose husband divorced her, except when had (punishment) is required. Meanwhile, Imam Shafi'i allowed the marriage of a pregnant woman to a man who did not impregnate her.